Frequency of Immunisation Status, Complications and Outcome in Children Admitted with Measles in Public and Private Sector Hospitals of Karachi - Musarrat Ameer; Sina Aziz; Shaista Ehsan; Ume Kulsoom (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: To assess the immunisation status, frequency  of  complications  and  the  outcome  in  chil-  dren admitted with measles in public and private sector hospitals of Karachi. Methods: In this cross-sectional study a total  of  382  patients  admitted  with  measles,  of  either  sex  from 3 months to 13 years, who presented from March 2016 to March 2017 were included. A total of 265 (69.3%) children were from Ziauddin University Hospital (ZU) and  117  (30.6%)  from  Abbasi   Shaheed Hospital (AS). Non-probability convenient sampling technique was  used.  Those  with  con-  genital anomalies and chronic medical illnesses were excluded from the study. Detailed history  and  physical examination was done, and findings entered in a  Proforma.  Immunisation  status  of  the  pa- tients was recorded. All the patients were observed for complications like encephalitis,  pneumonia,  diarrhea, otitis media, epiglottis, febrile fits and  corneal  ulcers.  Statistical  analysis  was  done  using  SPSS version 22. Categorical values were compared by chi-square test, p-value of  <0.05  was  con- sidered significant. Results: A total of 382 were patients admitted with measles, 265 (69.3%) from  Ziauddin  University  hospital and 117 (30.6%)  from  Abbasi  Shaheed  Hospital.  Overall,  57.4%  were  completely  vaccinated in ZU vs. 32.5% in AS. Despite being completely vaccinated, children in ZU; 152/265 (80%) and in AS; 38/117 (30.6%) had complications with a statistically significant (p<0.0001) difference between private     and government sector hospitals.  Predominantly,  in  both  hospitals  pneumonia  was  common  followed by gastroenteritis. Overall mortality was 13/382 (3.4%) in both hospitals combined. Conclusion: A sizeable number of children admitted with measles in both private and  government  hospitals were unvaccinated. A significant number developed measles despite receiving two doses of vaccine. Frequency of complications was higher in private versus government hospitals. Mortality from measles was high (3.4%) especially in the unvaccinated.